2011
DOI: 10.1016/j.cell.2011.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Riboneogenesis in Yeast

Abstract: Summary Gluconeogenesis converts three carbon units into glucose. Here we identify an analogous pathway in Saccharomyces cerevisiae for converting three carbon units into ribose, a component of nucleic acids and nucleotides. This riboneogenic pathway involves the enzyme sedoheptulose-1,7-bisphosphatase (SHB17), whose activity was identified based on accumulation of sedoheptulose-1,7-bisphosphate in the corresponding knockout strain. We determined the crystal structure of Shb17 in complex with sedoheptulose-1,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
129
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 55 publications
(48 reference statements)
7
129
1
Order By: Relevance
“…To confirm the identity of these enzymatic products, we showed that the fructose 1-phosphate formed exhibited a retention time and MS/MS spectra identical to those of the standard of fructose 1-phosphate. Similarly, the sedoheptulose 1-phosphate synthesized was also shown to exhibit a retention time and MS/MS spectra identical to those previously reported (29). In addition, these products exhibited retention times and MS/MS spectra identical to those FIGURE 2.…”
Section: Increased Levels Of Fructose 1-phosphate and Sedoheptulose 1supporting
confidence: 68%
See 2 more Smart Citations
“…To confirm the identity of these enzymatic products, we showed that the fructose 1-phosphate formed exhibited a retention time and MS/MS spectra identical to those of the standard of fructose 1-phosphate. Similarly, the sedoheptulose 1-phosphate synthesized was also shown to exhibit a retention time and MS/MS spectra identical to those previously reported (29). In addition, these products exhibited retention times and MS/MS spectra identical to those FIGURE 2.…”
Section: Increased Levels Of Fructose 1-phosphate and Sedoheptulose 1supporting
confidence: 68%
“…Fructose 1-phosphate formed from the enzymatic reaction exhibited the same retention time and MS/MS spectra as the commercial standard (fructose 1-phosphate). Sedoheptulose 1-phosphate synthesized using the two different methods also exhibited the same retention times and MS/MS spectra as reported previously (29). The commercial standard of fructose 1-phosphate was used for quantification of the endogenous metabolic intermediates.…”
Section: Analysis Of Sugar Phosphates and Nad(h)-mentioning
confidence: 75%
See 1 more Smart Citation
“…The reactions of SBA and SBPase are characteristic of the regeneration part of the Calvin cycle in photosynthetic organisms (11), and overproduction of SBPase in tobacco was shown to enhance carbon assimilation and crop yield (12). Recently, Saccharomyces cerevisiae was shown to possess a promiscuous SBPase encoded by SHB17, which also has FBPase and octulose-bisphosphatase (OBPase) activity and operates in the riboneogenesis pathway (13). It is possible that a promiscuous bisphosphate aldolase is active as both FBA and SBA and also that a bisphosphatase active as FBPase and SBPase exists.…”
mentioning
confidence: 99%
“…11) Metabolomics is a scientific study that aims to identify and quantify the levels of all metabolites; it has been applied widely in many areas, such as medicine, biology, and food science. [12][13][14][15] GC-MS is an analytic method used frequently in metabolomics studies to examine low-molecular-weight metabolites, because GC-MS provides heightened equipment stability and user-friendly tools for data analysis. 16,17) This paper evaluates, through the use of GC/ MS-based metabolomics, the effect of acute hydrogen sulfide poisoning on the metabolic profiles of rats.…”
mentioning
confidence: 99%